2014
DOI: 10.5301/jabfm.5000166
|View full text |Cite
|
Sign up to set email alerts
|

Shear Bond Strength of Self-Adhering Flowable Composite on Dentin with and without Application of an Adhesive System

Abstract: Although SBS values of Vertise Flow groups were lower than those for conventional flowable resin composite groups, with further developments in material technology, self-adhering materials could be promising materials especially for pediatric dentistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
46
0
12

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 24 publications
11
46
0
12
Order By: Relevance
“…The present study compared the SBS of two flowable composites after SiC or laser pretreatment of primary tooth surfaces. As in previous studies (Juloski et al, ; Salerno et al, ; Tuloglu et al, ; Vichi et al, ; Yazici et al, ), the materials and methods used for surface pretreatment influenced SBS to enamel and dentin. Cavity preparation by burring or SiC leads to the formation of a smear layer (Baraba et al, ) on the tooth surface, which can be removed by chemical means.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The present study compared the SBS of two flowable composites after SiC or laser pretreatment of primary tooth surfaces. As in previous studies (Juloski et al, ; Salerno et al, ; Tuloglu et al, ; Vichi et al, ; Yazici et al, ), the materials and methods used for surface pretreatment influenced SBS to enamel and dentin. Cavity preparation by burring or SiC leads to the formation of a smear layer (Baraba et al, ) on the tooth surface, which can be removed by chemical means.…”
Section: Discussionsupporting
confidence: 54%
“…To create a flat surface through the central dentin, the incisal edge of the tooth was removed with a diamond wheel (Vichi et al, ). A standardized smear layer was obtained by polishing with 600 grit waterproof SiC for 1 min (Bektas et al, ; Scaminaci Russo et al, ; Tuloglu et al, ; Vichi et al, ; Yazici et al, ). The same subgroup divisions as described for enamel molds were prepared for dentin molds ( n = 10, groups 7–12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies mentioned that when using high energy laser tends to melt the irradiated dentin, alters and denatures collagen fibers, closes tubules, and prevents bonding infiltration in opened tubules and the formation of resin tags [12]. Tuloglu et al [34] evaluated the shear bond strength of conventional and self-adhering resin composite to dentin and they found that SBS values of self-adhering resin composite are lower than conventional ones whether they are bonding to lacteal or permanent teeth. Moreover Russo et al [35] concluded that Er:YAG laser irradiation prior to bonding has increased the SBS values of all adhesive systems used including self-adhering resin composite.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have demonstrated increased circumferential stiffness (Chuang et al, 2007), yield stress, and resilience (Slusarewicz et al, 2011) of annular tissue. Such effects also extend to the intervertebral joint behavior including changes in axial neutral zone parameters (Barbir et al, 2010; Yerramalli et al, 2007), flexion-extension neutral zone parameters (Hedman et al, 2006; Kirking et al, 2013), and maximum disc bulge during axial loading (Slusarewicz et al, 2011). It was hypothesized that changes in the disc mechanical behavior with cross linking would also extend to an increased resistance against shearing of the interlamellar interface.…”
Section: Introductionmentioning
confidence: 99%